(untitled) (Semiárida, 2020)
The purpose of the present study was to evaluate the effect of soil environment on yield and response of three wheat cultivars to fertilization with three doses (0, 40 and 120 kg.ha-1). The differences were analyzed with analysis of variance and Fisher’s LSD test. Gross margins of each treatment were calculated. All four factors tested in this experiment (site, environment, cultivar and fertilization) had a significant influence on crop performance. Yield and fertilization response were related to water availability which differed among environments. The yield component that most affected yield was the number of grains per square meter, showing strong variability among treatments (5000 to 15000 g.m-2). These differences produced a wide range of variation in gross margins between environments, where a negative effect of fertilization in the more moisture limited environment could be observed, while in those with less moisture restrictions a positive contribution of fertilization to gross margin was found.